SMALL HYDROPOWER PLANTS IN SLOVENIA - Mavsar, Mavsar (Journal of Energy Technology, 2024)
In this article, an overview of the small hydropower (SHP) sector in Slovenia and the EU is given. Data were collected from publically accessible statistics (SURS and EUROSTAT) and public documents available on the internet. The gross production of electric energy from small hydropower plants, its share in production from renewable sources, available hydrological potential, trends in SHP sector and strategic development for the future are all considered. EU experts optimistically predict increasing SHP capacities while the statistical data for the previous decade show the opposite.